Superconductivity and fluctuating magnetism in quasi-two-dimensional kappa-(BEDT-TTF)(2)Cu[N(CN)(2)]Br probed with implanted muons - Lancaster, T; Blundell, S; Pratt, F; Schlueter, J (2011)
A muon-spin relaxation (μ+SR) investigation is presented for the molecular superconductor κ-(BEDT-TTF) 2Cu[N(CN) 2]Br. Evidence is found for low-temperature phase separation throughout the bulk of the material, with only a fraction of the sample showing a superconducting signal, even for slow cooling. Rapid cooling reduces the superconducting fraction still further. For the superconducting phase, the in-plane penetration depth is measured to be λ ||=0.47(1)μm, and evidence is seen for a vortex decoupling transition in applied fields above 40 mT. The magnetic fluctuations in the normal state produce a precipitous drop in relaxation rate above 100 K, and we discuss the possible causes for the unusual relaxation that we observe for T>T c. © 2011 American Physical Society.